Social Determinants of Health Protection in Russia: Challenges and Proposed Solutions - N. E. Karpachev; V. S. Goryachev; S. A. Bazhenova (Здоровье мегаполиса)
Background. The article studies health as a factor of human well-being, economic productivity, and national social development. Social issues of health protection affect life’s quality and longevity in Russia. Purpose. To analyze social health determinants and their effect on the Russian health protection system, detect key problems and focus on their possible solutions. The objectives of the study are analyzing current social issues of health protection, investigating the impact of inequality and economic conditions on population health, and considering the role of education and culture in health maintenance. Materials and methods. The article scrutinizes Russian regulatory acts on health protection, WHO research papers, studies of national and international authors, and social studies on health protection. The authors highlight the following: the concept of health in sociology, social and economic determinants of health, factors of health protection, innovations in healthcare, working conditions and labor protection, national healthcare policy, and improvement of social and economic factors of health protection. Normative target-based, statistical, comparative methods, and social and system-analytical analyses were used in this article. Results. Today, uneven resources, insufficient funding, and staff imbalance put a negative effect on the health protection system. The current healthcare policy needs to reform the organizational and economic mechanisms of the health protection system. Finance optimization, emphasis on primary care, healthy lifestyle promotion, and early disease detection are more productive than advanced case treatment.